Identification of a guanine nucleotide exchange factor for Arf3, the yeast orthologue of mammalian Arf6. - Alison K Gillingham; Sean Munro (PLoS ONE)
Small G proteins of the Arf and Rab families are fundamental to the organisation and activity of intracellular membranes. One of the most well characterised of these G proteins is mammalian Arf6, a protein that participates in many cellular processes including endocytosis, actin remodelling and cell adhesion. Exchange of GDP for GTP on Arf6 is performed by a variety of guanine nucleotide exchange factors (GEFs), principally of the cytohesin (PSCD) and EFA6 (PSD) families. In this paper we describe the characterisation of a GEF for the yeast orthologue of Arf6, Arf3, which we have named Yel1 (yeast EFA6-like-1) using yeast genetics, fluorescence microscopy and in vitro nucleotide exchange assays. Yel1 appears structurally related to the EFA6 family of GEFs, having an N-terminal Sec7 domain and C-terminal PH and coiled-coil domains. We find that Yel1 is constitutively targeted to regions of polarised growth in yeast, where it co-localises with Arf3. Moreover the Sec7 domain of Yel1 is required for its membrane targeting and for that of Arf3. Finally we show that the isolated Yel1 Sec7 domain strongly stimulates nucleotide exchange activity specifically on Arf3 in vitro.